Fire-Resistant Geopolymers : Role of Fibres and Fillers to Enhance Thermal Properties /: Role of Fibres and Fillers to Enhance Thermal Properties. (2014) - Vickers, Les; van Riessen, Arie; Rickard, William D. A
No abstract available